Pemanfaatan Media Sosial dalam Mewariskan Nilai-Nilai Akhlak KH. Hasyim Asy‘ari di Kalangan Mahasiswa Pendidikan Agama Islam - Putri Salma; Syifa Fajriyah; Fikron Yunus; Abdul Fadhil (Advances In Education Journal, 2025)
This study explores how social media is used to transmit the moral teachings of KH. Hasyim Asy‘ari among students of Islamic Religious Education. The research aims to analyze the relevance, forms of internalization, and impact of digital platforms in strengthening classical Islamic ethics in contemporary academic settings. Using a qualitative library research method, data were collected from primary texts of KH. Hasyim Asy‘ari, journal articles, and digital content produced. The findings show that social media enables wider dissemination of moral values, encourages creative forms of da’wah, and supports character formation through everyday digital practices. However, challenges arise from misinformation, digital distractions, and inconsistencies in content production. The study concludes that social media can effectively sustain KH. Hasyim Asy‘ari’s ethical teachings when supported by strong digital literacy and values-based communication strategies.